Determinants of behavioural intention to use interactive data extraction analysis among company field tax auditors of IRBM branch in Klang Valley - Muniza, Mukhiar (2024)
The Inland Revenue Board of Malaysia (IRBM) has introduced the Interactive Data Extraction Analysis (IDEA) auditing software intending to improve the productivity and efficiency of field tax auditors. The implementation of numerous data analysis and enhancement techniques, such as IDEA, aims to enhance the current work processes. Nevertheless, the utilisation of IDEA in the current work process for IRBM company field tax auditors remain minimal, as indicated by the limited number of company field tax auditors using it. This study aims to uncover the factors that influence a company field tax auditor’s inclination to use an existing auditing software in the workplace. The research approach utilised the Unified Theory of Acceptance and Use of Technology (UTAUT) as the framework, combining attitude and training as independent variables. The data were gathered from a sample of 212 company field tax auditors from eight localities in the Klang Valley branches, including Wangsa Maju, Cheras, Bangi, KL Bandar, Petaling Jaya, Duta (Perniagaan), Shah Alam, and Klang. This was done by administering a well-structured questionnaire. The Statistical Package for Social Science (SPSS) is employed to conduct descriptive analysis, validity testing, reliability testing, and regression analysis on the six hypothesized relationships. The results showed that attitude, performance expectancy and effort expectancy were significantly influenced behavioural intention to use IDEA auditing software. The other variables, which are social influence, facilitating condition, and training, are found not to have a significant influence on behavioural intention to use IDEA auditing software. The study hoped to assist the IRBM in future planning and developing strategies to encourage company field tax auditors to utilise IDEA auditing software in the future.